2006
DOI: 10.7205/milmed.171.11.1147
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Temporomandibular Disorders in War Veterans with Post-Traumatic Stress Disorder

Abstract: The purposes of this study were to assess the prevalence of temporomandibular disorders in Croatian war veterans suffering from post-traumatic stress disorder (PTSD) and to analyze the impact of the disease on mandibular function. One hundred eighty-two male subjects participated in the study. The examined group consisted of 94 subjects who had taken part in the war in Croatia and for whom PTSD had previously been diagnosed. Patients were compared with an age- and gender-matched group of subjects who had not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
2
18
1
1
Order By: Relevance
“…(226)[16] studied the prevalence of TMJ disorders in war veterans with PTSD and found that TMJ disorder is significantly higher in war veterans vs control group that did not have participant in war and PTSD that exactly same with the result of our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…(226)[16] studied the prevalence of TMJ disorders in war veterans with PTSD and found that TMJ disorder is significantly higher in war veterans vs control group that did not have participant in war and PTSD that exactly same with the result of our study.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies reported high prevalence of signs and symptoms of TMDs[16] and temporomandibular joint[17] in war veterans who suffered from PTSD. Uhac et al .…”
Section: Introductionmentioning
confidence: 99%
“…From these, six meet the inclusion criteria [6][7][8][17][18][19] . One paper was excluded because it did not evaluate the relationship between TMD and PTSD 20 and five because they did not use diagnostic criteria validated for TMD, only evaluating signs and symptoms of dysfunction in the studied population [21][22][23][24][25] . The flowchart with the article selection process is shown in figure 1, and the information of the studies included in the review is shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…В большинстве случаев важную роль играют психологические факторы [23]. Посттравматическое стрессовое расстройство повышает риск развития дисфункции ВНС [24]. У значительной ча-сти таких пациентов отмечается высокий уровень депрес-сии и соматизации [25].…”
Section: не зубная лбunclassified